Surface Mo or Ni-Enrichment Applied to Granulated Self-Lubricating Composites: Microstructural and Tribological Evaluation - Damin, Keli Vanessa Salvador; Tasior, Gabriel da Rosa; Hammes, Gisele; Klein, Aloisio Nelmo; de Mello, José Daniel Biasoli; Bendo, Tatiana; Binder, Cristiano (Frontiers in Mechanical Engineering, 2022)
Sintered self-lubricating components may present inappropriate mechanical properties despite their excellent tribological properties. In general, alloying elements are used to improve these properties but with a cost increase. As an alternative, surface enrichment (or surface alloying) with alloying elements may be applied. This study developed and characterised sintered composite materials surface-enriched with nickel or molybdenum. The results showed that the surface enrichment process is attractive for increasing the tribomechanical properties. The Mo-enriched samples presented superior tribological results. Compared with the reference samples (not enriched), Mo-enriched specimens showed an increase of 4954% in scuffing resistance, lower friction coefficient (0.09) and reduced wear rate (68% and 96% lower for the specimen and the counter body, respectively). These results were mainly attributed to microstructural modification.